Measuring Information Security Awareness of Indonesian Smartphone Users - Puspita Kencana Sari; Candiwan Candiwan (Universitas Ahmad Dahlan, 2014)
One of information security management elements is information security awareness program. Usually, this programs only involve the employees within the organization. Some organizations also consider security awareness for some parties outside the organization like providers, vendors, and contractors. This paper add consumers as variable to be considered in information security awareness program as there are also some threats for organization through them. Information security awareness will be measured from user’s knowledge, behavior, and attitude of five information security focus areas in telecommunication, especially related with smartphone users as one segment of telecommunication provider. For smartphone users, information security threats not only from Internet, but also by phone call or texting. Therefore, focus area in this research consist of adhere to security policy, protect personal data, fraud/spam SMS, mobile application, and report for security incident. This research use analytic hierarcy process (AHP) method to measure the information security awareness level from smartphone users. In total, the result indicated that awareness level is good (80%). Although knowledge and attitude dimension are in good criteria of awareness level, but behaviour dimension is average. It can be a reason why there are still many information security breach against smartphone user despite good awareness level.